Elektroniczne bazy danych w usługach informacyjnych biblioteki akademickiej - Kościewicz, Dawid (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The aim of the paper is to discuss the challenges for providing effective scientific information in an economic library, in the context of use of electronic databases. The electronic databases subscribed by the Main Library of the Wrocław University of Economics are described, regarding the challenges for their use by the Library`s users. The article is based on a subject literature from the field of science of librarian studies, as well as on the author`s personal experience and observations. The paper ends with following conclusions: academic libraries have to conduct an effective information education of their users; increasing the information competences of users, regarding databases, should be a priority of librarians charged with scientific information; a beneficial form of enriching academic library`s information resources is reaching for information sources of the European Union.